Security Intelligence Services in New Democracies - Williams, K. author. aut Link
IX, 291 p.
Keywords: The first account of the secret police in Eastern Europe and after 1989, this book uses a wide range of sources, including archives, to identify what has and has not changed since the end of communism. After explaining the structure and workings of two of the area's most feared services, Czechoslovakia's StB and Romania's Securitate, the authors details the creation of new security intelligence institutions, the development of contacts with the West, and forms of democratic control.